2011
DOI: 10.1007/s12206-011-0529-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microstructure and chemical composition on cold crack susceptibility of high-strength weld metal

Abstract: The effects of the microstructural constituents, chemical composition, and retained austenite on high-strength weld metal were studied using preheat-free steels and GMAW solid wires with a low hydrogen content. The cold cracking susceptibility of these GMAW wires was evaluated using the y-groove Tekken test. The results showed that acicular ferrite produced the greatest resistance to cold cracking and that the microstructure of the deposit was more important than the hardness and diffusible hydrogen content in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 13 publications
3
10
0
Order By: Relevance
“…The brittle trans-granular fracture is typical for the cold cracking. [1][2][3] One of the influence on the cold cracking susceptibility of high strength steel welds has microstructural constituents and chemical composition, Yi and col. [4] found out, the that acicular ferrite produced the greatest resistance to cold cracking and the retained austenite had no effect on the cold cracking susceptibility at a low preheating temperature. Alloying elements for nucleating acicular ferrite, such as Ti, Al, and V, are required for proper austenite grain size.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The brittle trans-granular fracture is typical for the cold cracking. [1][2][3] One of the influence on the cold cracking susceptibility of high strength steel welds has microstructural constituents and chemical composition, Yi and col. [4] found out, the that acicular ferrite produced the greatest resistance to cold cracking and the retained austenite had no effect on the cold cracking susceptibility at a low preheating temperature. Alloying elements for nucleating acicular ferrite, such as Ti, Al, and V, are required for proper austenite grain size.…”
Section: Introductionmentioning
confidence: 88%
“…It was found that, without preheat weld deposits (< 5 ml/100 g) did not crack whereas all those weld metals (> 5 ml/100 g) exhibited cold cracking. The researchers use mostly the Y groove Tekken test [4,6] or the Gapped bead-on-plate test(G-BOP) [5,[8] for an evaluation of the welds cold cracking susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…The desired fine-grained microstructure is often achieved in welding using an optimal thermal cycle [ 7 , 8 , 9 ] and through minimizing the content of impurities and segregations making the grain structure more refined [ 10 ]. Another effective metallurgical solution is to refine the microstructure using a mechanism of heterogeneous grain nucleation at non-metallic inclusions and acicular ferrite when refractory oxides, sulfides, and nitrides are formed [ 11 ]. The most effective method for refining the microstructure is to design special welding wires and introduce rare earth metals (REMs) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, cold cracking or hydrogen embrittlement (HE) may occur in relation to welding due to a critical combination of susceptible high-strength microstructure, stress state, and hydrogen absorption. [4,5] In particular, the high diffusivity of hydrogen is regarded as favoring embrittlement. [6] Weldingrelated residual stresses and changes in microstructure as well as external loading in addition to facilitate hydrogen diffusion, whereby a local critical accumulation in stress-concentrated regions and thus the risk of embrittlement increases.…”
Section: Introductionmentioning
confidence: 99%